A comparative study of a bio fuel cell with two different proton exchange membrane for the production of electricity from waste water; Resource-Efficient Technologies; Vol. 3, iss. 1 : TECHNOSCAPE 2016: International Conference on Separation Technologies in Chemical, Biochemical, Petroleum and Environmental Engineering - Shahi A. Amrita (2017, 2017)
Title screen